10.1007/s00127-012-0490-0 (CrossRef Listing of Deleted DOIs, 2000)
PURPOSE: A growing emphasis on autonomy, manifest through the influence of recovery orientations, user involvement, and the broader shift towards patient-centered healthcare, has significantly influenced mental health care. The Convention on the Rights of Persons with Disabilities (CRPD) is a pivotal development in this regard, challenging longstanding practices in mental health care and particularly involuntary care. This study examined how European mental health legislation seeks to promote the autonomy of those subjected to involuntary care, by analyzing laws from 27 jurisdictions. METHODS: Data was collected via a comprehensive survey between July 2023 and September 2024, completed by country representatives from the EU COST Action FOSTREN network. We examined the letter of the law as regards 16 autonomy-promoting provisions including the principle of least restriction, capacity-based criteria, supported decision-making, advance healthcare directives, treatment plans, rights to appeal, legal aid, advocacy services, and oversight mechanisms. RESULTS: Most laws across the 27 jurisdictions were amended in the last eight years. All legislations included at least one measure related to the principle of least restriction, the right to appeal against involuntary status, and support to do so, such as legal aid. In contrast, mechanisms designed to support autonomous decision-making, such as Advance Healthcare Directives and Supported Decision-Making, were less frequently included as a right. CONCLUSION: While procedural legal safeguards are well established, there is significant variation in the adoption of other legal mechanisms to afford statutory rights to individuals in line with autonomy promoting approaches, including the CRPD.